Pengembangan Berbasis Multimedia Interaktif Menggunakan Articulate Storyline 3 pada Pembelajaran - M. Luqmanul Hakim Habibie (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to: 1) develop interactive multimedia-based teaching materials using Articulate Storyline 3 for fifth-grade science learning in Islamic elementary schools (MI/SD), 2) assess the feasibility of these materials, 3) evaluate their appeal to students and educators, and 4) examine their effectiveness in science instruction. This research follows the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) and was conducted at MIN 1 Bandar Lampung and MIN 7 Bandar Lampung. Data were collected through questionnaires. The results indicate that the interactive multimedia-based teaching materials were developed systematically, adhering to the ADDIE framework, which includes analysis, design, production, and product revision. The materials were deemed highly feasible based on validation by media, content, and language experts. Additionally, both educators and students responded positively, confirming the materials' high appeal. Furthermore, the developed interactive multimedia-based teaching materials proved effective in enhancing science learning. In conclusion, this study successfully produced interactive multimedia-based teaching materials that are feasible, engaging, and effective for fifth-grade science instruction. The developed product is suitable for implementation in the learning process.